War-child mothers in northern Uganda: the civil war forgotten legacy. Issue 3 (3rd April 2017) - Mukasa, Norman
ABSTRACT: The protracted LRA war in northern Uganda was characterised by the abduction and abuse of an unknown but significant number of girls and women. These girls were forced to carry guns and become wives to rebels, among other roles during captivity. Based on thirteen child mothers' interviews and eight key informant interviews, the study found that the lives of formerly abducted mothers are tainted with stigma, rejection, and discrimination by in-laws, relatives, and the community, which leads to identity problems and limited possibilities for their integration. Child mothers' return to school, small business engagement, and social involvement reduced their plight.